Ocular prosthesis rehabilitation in patients with phthisis bulbi : A case report - Nurrahma, Rifaat; Dammar, Irfan (Hasanuddin University, 2022)
Objective: Phthisis bulbi is an eye condition that happens when a wound heals slowly because of a severe eye injury, inflammation, or neoplasm. It is an end-stage eye disease that causes the eyeball and the contents inside the eye to shrink and become disorganized. Eye-related disfigurement can cause a lot of physical and emotional trouble. Instead of surgery like enucleation or evisceration, prosthetic rehabilitation of the remaining eyeball is the most effective treatment for the phthisis bulbi. Rehabilitation of these patients is challenging, and a multidisciplinary approach is needed to make an ocular prosthesis that works well.Methods: A 25-year-old male patient presented to the department of Prosthodontics at Hasanuddin University Dental Hospital with the chief complaint of vision loss in his left eye and an unattractive appearance due to a bulging white spot regressing eyeball. The patient previously used a contact lens but was satisfied with the results. The treatment plan involves the fabrication of a custom-made acrylic resin eye prosthesis. Custom ocular prostheses are created using impression techniques that provide retention benefits.Results: After twenty-four hours, one week, and six months after implantation, follow-up appointments revealed no inflammation and excellent adaptation of the ocular prosthesis. Conclusion: The custom-made ocular prosthesis presented in this case can be used to give the phthisis bulbi patient a more natural appearance. Using a custom ocular prosthesis with the proper size, color, and color can yield an acceptable aesthetic result